2022
DOI: 10.3390/polym14061202
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Hydrogels Based on the Diels–Alder Click Reaction: Rheological and Kinetic Study

Abstract: The Diels–Alder reaction is recognized to generate highly selective and regiospecific cycloadducts. In this study, we carried out a rheological and kinetic study of N-furfuryl chitosan hydrogels based on the Diels–Alder click reaction with different poly(ethylene)glycol-maleimide derivatives in dilute aqueous acidic solutions. It was possible to prepare clear and transparent hydrogels with excellent mechanical properties. Applying the Winter and Chambon criterion the gel times were estimated at different tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Considering the rheological data obtained by the amplitude and frequency sweep tests, in Figure 8, it is illustrated the effect of water content and NH 2 /CHO ratio of the hydrogels on the γ l and the loss tangent (tan δ = G"/G ). The loss tangent, tan δ, gives the information about the viscoelasticity degree of the material in the investigation conditions: tan δ > 1 is characteristic for liquid-like materials, and tan δ < 1 is characteristic for solid-like materials [45]. The widest ranges of linear viscoelasticity were recorded for the hydrogels with NH 2 /CHO ratios up to 3, with double water amount (Figure 8a).…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Considering the rheological data obtained by the amplitude and frequency sweep tests, in Figure 8, it is illustrated the effect of water content and NH 2 /CHO ratio of the hydrogels on the γ l and the loss tangent (tan δ = G"/G ). The loss tangent, tan δ, gives the information about the viscoelasticity degree of the material in the investigation conditions: tan δ > 1 is characteristic for liquid-like materials, and tan δ < 1 is characteristic for solid-like materials [45]. The widest ranges of linear viscoelasticity were recorded for the hydrogels with NH 2 /CHO ratios up to 3, with double water amount (Figure 8a).…”
Section: Rheological Propertiesmentioning
confidence: 99%
“…While the furan-maleimide reaction proceeds at room temperature, it generally requires a long time. In this context, recent studies have shown that the rate of cycloaddition reaction could be accelerated by increasing the temperature and choosing a suitable solvent. , More importantly, several reports demonstrate that the cycloaddition rate could be improved by using water as a solvent, which is desirable for fabricating hydrogels for biological applications. , In light of these observations, there is an ever-increasing interest in utilizing the DA cycloaddition reaction to fabricate hydrogels. Some of these examples are briefly discussed to highlight the diverse hydrogels accessed by using this approach.…”
Section: Diels-alder (Da) and Inverse Electron Demand Diels-alder (Ie...mentioning
confidence: 99%
“…Without the aid of additional techniques, quantitative information about the chemical conversion using mechanical techniques at any time or temperature is difficult to obtain except at the gel point in which a multifunctional DA precursor was used. For the forward kinetics, isothermal tests at various temperatures are often performed to measure the time until gelation. , Without a real-time technique like IR spectroscopy to monitor the conversion over time, the average reaction rate is measured up to the gel point on these isothermal tests, which can typically provide an accurate activation energy or enthalpy but maybe not a frequency factor or activation entropy. In their study of an elastomeric DA material using a bismaleimide (MM), Polgar et al separated the cross-linking rate into two forward rate equations: one for forming a furan–MM bond and another for forming a F–MM–F cross-link .…”
Section: Introductionmentioning
confidence: 99%
“…Other (DA) studies using rheometric methods for cross-linking kinetics ,, helped inspire the this work. Buonerba et al reported application of both Eyring and Arrhenius descriptions to differentiate the endo and exo rDA reactions in solvent using 1 H NMR .…”
Section: Introductionmentioning
confidence: 99%